Analisis Perbandingan Kesehatan Bank Domestik dan Bank Asing dengan Metode RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital) - Soelaeman Rasyid (STIE Indonesia Banking School, 2018)
The performance of national banking need not be doubted. Nine years ago, the total assets of commercial banks reached Rp. 1,469.8 trillion with outstanding loan disbursements of Rp. 695 trillion and deposits of Rp. 1,166 trillion. As of March 2014, total assets of commercial banks reached Rp. 4.933 trillion with outstanding credit of Rp 3,306.9 trillion and deposits of Rp 3,618.1 trillion. Based on this data then, of course, banking has become a potential money machine. As of November 2014, commercial banks posted a net profit of Rp. 98.5 trillion, jumping nearly 300 percent compared to 2005 (data: www.bi.go.id). Bank Indonesia as the Central Bank of Indonesia has established a policy on the soundness of commercial banks with a CAMELS method. This Regulation is set forth in Bank Indonesia Regulation No. Based on Bank Indonesia Regulation No. 6/10 / PBI / 2004 dated April 12, 2004. Bank Indonesia further improved the Bank’s health assessment method from CAMELS method to RGEC method (Risk Profile, Good Corporate Governance, Earning and Capital). 13 / PBI / 2014 concerning Commercial Bank Health Level. Health assessments using the RGEC method, assessed by Composite Rating. According to Refmasari and Setiawan (2014), the composite value for financial ratios of each component is valued as follows, 1). PK-1 is worth 5 (five), 2). PK-2 is worth 4 (four), 3). PK-3 is worth 3 (three), 4). PK-4 is worth 2 (two), 5). PK-5 is worth 1 (one). Risk Profile, assessment ofrisk profile can use some ratio, that is Non-Performing Loan (NPL), Liquidity Risk by using Loan to Deposit Ratio (LDR) measurement. Good Corporate Governance (GCG), there are three aspects of the assessment that must be met, namely Governance Structure, Governance Process, and Governance Output, Risk Rentability using several ratios, namely: ROA Ratio (Return On Asset), Net Interest Margin Ratio (NIM) Capital or Capital, Ratio that can measure capital factor that is ratio of CAR (Capital Adequacy Ratio).